2023
DOI: 10.3201/eid2905.221226
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Transmission Dynamics of Dengue in Large and Small Population Centers, Northern Ecuador

Abstract: Although dengue is typically considered an urban disease, rural communities are also at high risk. To clarify dynamics of dengue virus (DENV) transmission in settings with characteristics generally considered rural (e.g., lower population density, remoteness), we conducted a phylogenetic analysis in 6 communities in northwestern Ecuador. DENV RNA was detected by PCR in 121/488 serum samples collected from febrile case-patients during 2019–2021. Phylogenetic analysis of 27 samples from Ecuador and other countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
2
7
0
1
Order By: Relevance
“…These changes may have driven the uptick in DENV FoI in Esmeraldas and the Amazon, which were not previously considered high risk areas. In Esmeraldas, connectivity first increased with Colombia, consistent with the observation that the DENV serotypes circulating in Esmeraldas between 2010–2014 more closely matched those circulating in Colombia than the rest of Ecuador [ 34 , 36 , 62 ]. A more recent study demonstrated dissemination of DENV1 and DENV2 from urban centers to more isolated communities in the Esmeraldas province [ 36 ].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…These changes may have driven the uptick in DENV FoI in Esmeraldas and the Amazon, which were not previously considered high risk areas. In Esmeraldas, connectivity first increased with Colombia, consistent with the observation that the DENV serotypes circulating in Esmeraldas between 2010–2014 more closely matched those circulating in Colombia than the rest of Ecuador [ 34 , 36 , 62 ]. A more recent study demonstrated dissemination of DENV1 and DENV2 from urban centers to more isolated communities in the Esmeraldas province [ 36 ].…”
Section: Discussionsupporting
confidence: 78%
“…Consistent with this observation, CHIKV caused an outbreak in rural and highly isolated communities in Esmeraldas only in 2019, long after the major chikungunya epidemic across Ecuador in 2015 [ 65 ]. As previously low-population rural areas become increasingly urbanized and connected to other rural areas and to major cities, their role in maintaining transmission and helping reseed epidemics is expected to increase [ 36 , 66 ]. Further, lack of infrastructure often tracks with rapid urbanization, and may result in limited water access, garbage collection, and sewage, which are all local arboviral disease risk factors in Ecuador [ 23 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study from febrile case-patients during 2019-2021 published by Márquez et al, reports two possible introduction events of DENV-2 to Ecuador [22]. The first event involved a strain that arrived before 2009 and circulated until 2015.…”
Section: Discussionmentioning
confidence: 99%
“…The second event involved a strain that arrived in 2013, resulting in an Ecuadorian lineage that still persists and shares a high degree of similarity with sequences from Colombia and Venezuela [22]. These studies with human samples are consistent with our results, as the isolated genome from the vector shows a greater similarity to genomes from Colombia and Venezuela, as reported from virus sequences from human serum from dengue cases from the same locality [22]. The reported DENV-2 genome from mosquitoes also forms a cluster with sequences from other countries in the Americas.…”
Section: Discussionmentioning
confidence: 99%
“…In Ecuador, dengue fever is spread mainly by DENV-1 and DENV-2 viruses [ 14 ]. Malaria is predominantly caused by P .…”
Section: Introductionmentioning
confidence: 99%